DEVELOPMENT OF STUDENTS' MORAL ATTITUDE BASED ON AXIOLOGICAL APPROACHES - Musurmonov Ochilboy O‘razali o‘g‘li (Web of Journals Publishing, 2024)
The main content of this article is that the methods of developing moral attitudes based on axiological approaches to students using tools that can fully meet the requirements of today's time are explained in detail.
Keywords: Education, traditional worldview, moral relations, society, value, political maturity, development, axiological approach, moral maturity.